Applying of vent DNA polymerase for the amplification of D17S5 (YNZ22) alleles by PCR - Giang, Nguyen Hoai; Phuc, Nguyen Hanh; Kim Tuyen, Le Thi (Academia Journal of Biology, 2015)
Applying of vent DNA polymerase for the amplification of D17S5 (YNZ22) alleles by PCR